Molecular characterisation of fowl adenovirus associated with hydropericardium hepatitis syndrome in broiler and layer breeders in Azerbaijan - Erhan Bayraktar; Ozge Aydin; Hasan Emre Tali; Semaha Gul Yilmaz; Aysun Yilmaz; Nuri Turan; Ozge Erdogan Bamac; Akay Ozturk; Altug Erdem; Metin Kelleci; Jean-Remy Sadeyen; Pengxiang Chang; et al. (BMC Veterinary Research, 2024)
Abstract Background Fowl adenovirus-4 is a causative agent of hydropericardium hepatitis syndrome (HHS) in chickens and has been frequently reported from many countries. Fowl adenoviruses cause severe disease and mortality in broiler and layer breeders in Azerbaijan. Therefore, in this study, pathological lesions and the dissemination of fowl adenovirus-4 into the visceral organs of infected birds were investigated as well as molecular characterisation of detected strains. For this, liver, heart and spleen from 20 necropsied chickens originated from a broiler breeder flock and a layer breeder flock were embeded on the FTA cards and the samples were analysed for adenovirus-DNA by PCR and sequencing. Results The findings of necropsy in both broiler and layer breeder chickens were similar, and the liver was severely effected showing hepatitis, and the heart with hydropericardium lesions. The kidneys were swollen with haemorrhages and small white foci on the surface of the spleens were noted. Intestinal congestion and ecchymotic hemorrhages were also observed in some birds. Fowl adenovirus-4-DNA was detected by PCR in all collected organs of 20 birds. The sequence analysis revealed that fowl adenovirus-4 present in Azerbaijan and close similarity of the hexon genes of the adenoviruses existing in the Middle East, North America, far east and Indian subcontinent were determined by phylogenetic analysis. However, sequence diversity was detected from the adenovirus strains circulating in Europe, North and South America. Conclusions This study indicates the impact of fowl adenovirus-4 on the poultry health and production, and improved disease control and prevention strategies are necessary to reduce the HHS disease in chickens in Azerbaijan.